Liquid Chromatographic Estimation of Leuprolide Acetate in Bulk and Microsphere Formulation - Pittala, Sandhya; Sastry, Vedula Girija; Krishna, Rapalli Vamshi; Dubey, Sunil Kumar; Singhvi, Gautam (Asian Journal of Chemistry, 2018)
Development of a sensitive, robust and validated analytical method for determination of an active drug in sample matrix is the key component to ensure identity, purity and quality of drug and formulations. The aim of the proposed work was to develop and validate a simple, rapid, sensitive, robust and cost effective high performance liquid chromatographic method for the estimation of leuprolide acetate in bulk and formulations for routine analysis. The method was developed using Supelco-C18 (150 × 4.6 mm, 5 μm) analytical column and mobile phase consisting of a mixture of 10 mM sodium acetate buffer and acetonitrile in 70:30 ratios. Developed method was validated as per ICH guidelines. The method has demonstrated linearity over the range of 1 to 50 μg/mL with regression equation, peak area = 7364.6 × concentration (μg/mL) - 10051 (R2 = 0.998). The method demonstrated selectivity with no interference of formulation excipients and mobile phase. The developed method showed good and consistent recovery (98.85 to 101.05 %). Method indicated acceptable repeatability with % RSD not more than 1.58. The method was found to be sensitive with detection and quantification limit 0.26 and 0.79 μg/mL, respectively. Also, developed method was successfully applied for compatibility study and determination of entrapment efficiency of prepared microsphere formulation. The method was found to be accurate, precise, sensitive and selective for the determination leuprolide acetate in bulk and formulations.